The Dominican Republic Reader : History, Culture, Politics - González, Raymundo; Derby, Lauren; Roorda, Eric (Book collections on Project MUSE., 2014)
Despite its significance in the history of Spanish colonialism, the Dominican Republic is familiar to most outsiders through only a few elements of its past and culture. Non-Dominicans may be aware that the country shares the island of Hispaniola with Haiti and that it is where Christopher Columbus chose to build a colony. Some may know that the country produces talented baseball players and musicians; others that it is a prime destination for beach vacations. Little else about the Dominican Republic is common knowledge outside its borders. This Reader seeks to change that. It provides an intr.